PENGETAHUAN PASANGAN USIA SUBUR (PUS) TENTANG KANKER SERVIKS - Ari Shanti, Elvika Fit; Zholekhah, Dewi (Media Ilmu Kesehatan, 2016)
Background:Cervical cancer is a type of malignancy disease that is often found among women in Indonesia. It has a relatively high frequency until 25.6%. According to the Ministry of Health, there are about 100 cases per 100 thousand population or 200 thousand cases annually, and the cases of cervical cancer in Central Java increase year to year. The high mortality rate of cervical cancer in Indosnesia due to the lack of general knowledge about the dangers of cancer, the early signs of cancer, the risks factors for cancer, the ways to overcome it correctly, as well as to familiarize themselves with a healthy lifestyle. The treatment as early as possible is an important thing by giving counseling and information about Cervical Cancer. It is one of promoted action to prevent and reduce the cervical cancer. The long-term goal of this research is to analyze and explore health issues within the scope of midwifery. Objectif This study has the specific purpose of analyzing the effect of health education on maternal knowledge about Cervical Cancer In the village of Tambakrejo, Tempel, Sleman, Yogyakarta. This study is a part of an effort to deepen the understanding of health knowledge among the community, especially in the obstetrics field. Result : This study is a quasi-experimental approach to one group pre-test to post-test design. The populations in this study are all couples of reproductive age in the village of Tambakrejo, Tempel, Sleman Yogyakarta. Conclusion The statistical test used is paired samples test. The research results show that there are differences in knowledge before and after giving health education about cervical cancer (p = 0.0001 <0.05). The knowledge of cervical cancer when pre-test with a category is 3% increased to 37% at post-test. Health education provides increase the knowledge of cervical cancer among the fertile age couples. Keywords: Health Education, knowledge, Cervical Cancer